Development of ‘electronic circuit kit’ for the subject of design and technology - Ibrahim, A. H.; Tang, J. R.; Wan Ahmad, W. N.; Mei, J. H.; Azman, M. N. A. (AIP conference proceedings, 2023)
This study was conducted to develop ‘Electronic Circuit Kit’ as a Teaching Aid to facilitate the teaching and learning process of microcontrollers in the topic of Electronic Technology for the subject of Design and Technology (Form Two). This ‘Electronic Circuit Kit’ is produced based on the ADDIE Model. The ADDIE model covers five phases namely analysis, design, development, implementation and evaluation. The developed ‘Electronic Circuit Kit’ received validation from experts to evaluate the product in terms of functionality and product design. Findings of the study show that the developed ‘Electronic Circuit Kit’ can be adapted in learning the topic of Electronic Technology as the product meets the needs and requirements of learning standards. The design of ‘Electronic Circuit Kit’ is also found to be suitable for students and teachers. Further improvement will be focusing on the development of user manual with additional components on the ‘Electronic Circuit Kit’ such as electric motors and sensors to help vary the ideas in designing the circuit.